Solitary Sternal Metastases in a Patient with Nasopharyngeal Cancer Treated With Sternal Resection, Reconstruction with Polypropilen Mesh and Methylmetacrylate Mesh and Adjuvant Radiation Therapy (Annals of Medical Research, 2021)
None
Keywords: Nasopharyngeal cancer, Sternum, Metastases, Resection, Reconstruction, Radiation Therapy